UNBEATEN TRACKS IN JAPAN : LETTER I Tinjauan Women Travellers and Travel Writing - Akmal Jaya (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This research aims to show the influences of the power of discourse: genre, gender, and colonialism in Unbeaten Tracks in Japan by Isabella Lucy Bird. Some travel writing’s paradigms were used as theoretical background in this research, such Sara Mills and Carl Thompson. As an object of the research, the novel became the source of primary data. Another historical and cultural literary and also literary review of Unbeaten Tracks in Japan as secondary data. The result of the research examined that contestation of discourses implied the way of the author to preserve his stories.